Protection of Grapevine Pruning Wounds against Eutypa lata by Biological and Chemical Methods - Halleen, F.; Fourie, P.H.; Lombard, P.J. (South African Journal of Enology and Viticulture, 2016)
Eutypa dieback, caused by the fungus Eutypa lata, is a serious disease of grapevines that infects mainly through pruning wounds. The aim of this study was to evaluate the in vitro efficacy of fungicides from various chemical groups against E. lata, as well as the in vivo efficacy of the most effective fungicides and selected bacterial and fungal antagonists of E. lata, in grapevine pruning wound protection trials. In vitro studies revealed that flusilazole, tebuconazole, benomyl, fenarimol and myclobutanil were the most effective fungicides to inhibit mycelial growth of E. lata. Two field trials were conducted, one subjected to artificial inoculation and the second to natural infection only. In the first, benomyl, flusilazole and commercially available Trichoderma harzianum-containing products and an experimental Bacillus subtilis strain were applied to fresh pruning wounds. Two Cabernet Sauvignon vineyards were pruned in August 2001 and 2002 and immediately treated and inoculated with a spore suspension of E. lata one day later. Isolations were made from the treated pruning wounds after 12 months to assess the effectiveness of the treatments. The fungicides benomyl and flusilazole were the most effective treatments, although the Trichoderma treatments T77 and Trichoseal spray caused a significant reduction in E. lata infection. In a second trial, pruning wounds of Cabernet Sauvignon, Sauvignon blanc, Red Globe and Bonheur were treated with the Trichoderma products Vinevax (= Trichoseal spray) and Eco77 (= T77) in August 2005 and 2006, subjected to natural infection only and evaluated after seven months. Vinevax and Eco77 not only reduced E. lata, but they also reduced the incidence of other grapevine trunk disease pathogens.